Comparative field performance evaluation of different type of Pusa Electric Power Units - EKKA, UTPAL; SINGH, S P; SINGH, M K (The Indian Journal of Agricultural Sciences, 2022)
Pusa developed three walk-behind type electric power units were evaluated in 9.96 ha area for tillage in polyhouse,secondary tillage, planking and weeding-cum interculture operations at research farm of ICAR-IARI during kharif and rabi 2020 and 2021. The power of four-wheel and two-wheel electric power units was 350W while Pusa mini electric prime mover was having 450W power. The controlling-cum-guiding force for operation of four-wheel power unit, two- wheel power unit and mini electric prime mover was found 26.72, 30.9 and 22.7 N, respectively. Correspondingly, the draft force was 210, 245 and 300 N. Based on the rigorous field study, the effective field capacity with these electric power units were 2.3 times higher than manual operated four-wheel weeder for wide-row crops. The field efficiency with four-wheel, two-wheel electric power unit and mini electric prime mover was 78–83.26, 78.6–81.25 and 69.2–92.6% in weeding-cum-interculture operation, respectively. The walk-behind electric power units are also found to reduce operator’s drudgery by 80–85%. The mini electric prime mover was found 32.7% cheaper than the four-wheel and 17.2% than the two-wheel power unit. Its command area is one ha for secondary tillage and 5 ha for weeding-cum-interculture operations in wide-row crops.